Wilsons disease presenting as acute hepatic failure: A case report - Rashid, Harun Or; Das, Dulal Chandra; Mahtab, Mamun Al; Begum, Rokshana; Hossain, Sharker Mohammad Shahadat; Roy, Partho Protim; Rahman, Salimur (Bangladesh Medical Journal, 2016)
Abstract not available Bangladesh Med J. 2016 May; 45 (2): 110-112